An interferometric structure with a dual-resonance long period grating for strain sensing - Zawisza, R.; Jaroszewicz, L.R.; Mikulic, P.; Bock, W.J. (Opto-Electronics Review, 2018)
Spectral characteristics and amplitude tunability of a long period grating with a dual- resonance inside fiber loop mirror are studied in terms of applied stress caused by elongation. Inserting the polarization controller between grating and part of polarization maintaining fiber in the loop structure enables tuning of resonance and interferometric peaks. The maximum sensitivity of demonstrated sensor is of 1.943 dB/mε for the range of 1.1–4.4 mε. Combination of these two optical components allows to measure strain in a wider range comparing with sensors based on standard long period grating.